Experiences and challenges running CERN's high capacity tape archive. Issue 4 (December 2015) - Cancio, Germán; Bahyl, Vladimír; Kruse, Daniele Francesco; Leduc, Julien; Cano, Eric; Murray, Steven
Abstract: CERN's tape-based archive system has collected over 70 Petabytes of data during the first run of the LHC. The Long Shutdown is being used for migrating the complete 100 Petabytes data archive to higher-density tape media. During LHC Run 2, the archive will have to cope with yearly growth rates of up to 40-50 Petabytes. In this contribution, we describe the scalable setup for coping with the storage and long-term archival of such massive data amounts. We also review the challenges resulting and mechanisms devised for measuring and enhancing availability and reliability, as well as ensuring the long-term integrity and bit-level preservation of the complete data repository. The procedures and tools for the proactive and efficient operation of the tape infrastructure are described, including the features developed for automated problem detection, identification and notification. Finally, we present an outlook in terms of future capacity requirements growth and how it matches the expected tape technology evolution.